2009
DOI: 10.1186/1743-8977-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial cardiovascular effects of reducing exposure to particulate air pollution with a simple facemask

Abstract: Background: Exposure to air pollution is an important risk factor for cardiovascular morbidity and mortality, and is associated with increased blood pressure, reduced heart rate variability, endothelial dysfunction and myocardial ischaemia. Our objectives were to assess the cardiovascular effects of reducing air pollution exposure by wearing a facemask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
151
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 40 publications
7
151
1
4
Order By: Relevance
“…In the clinical setting, the removal of very high particle numbers by filters prevented the otherwise occurring arterial stiffness and increases of blood clotting (Bräuner et al, 2008). Similar observations were made in health subjects and patients with coronary heart disease that were wearing a very simple, yet highly efficient face mask while walking in highly polluted areas in Beijing, China (Langrish et al, 2009). Observations in healthy young volunteers exposed to pure elemental carbon particles implied that heart function was not affected by these controlled exposures.…”
Section: Clinical Studiesmentioning
confidence: 64%
See 1 more Smart Citation
“…In the clinical setting, the removal of very high particle numbers by filters prevented the otherwise occurring arterial stiffness and increases of blood clotting (Bräuner et al, 2008). Similar observations were made in health subjects and patients with coronary heart disease that were wearing a very simple, yet highly efficient face mask while walking in highly polluted areas in Beijing, China (Langrish et al, 2009). Observations in healthy young volunteers exposed to pure elemental carbon particles implied that heart function was not affected by these controlled exposures.…”
Section: Clinical Studiesmentioning
confidence: 64%
“…A few recently published clinical studies support pre-2005 studies that suggested increasing evidence for ultrafine particles in eliciting health effects during and after 2-hour exposure periods Langrish et al, 2009;Mills et al, 2011). However, most studies were performed with a mixture of particles and gases, which do not allow statements to be made about the contributions of ultrafine particles.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Interestingly, it was recently reported in a crossover study of 15 healthy individuals that systolic BP was significantly lower (114 versus 121 mm Hg) during a 2-hour walk in Beijing, China, while the subjects were wearing a high-efficiency particulate-filter facemask than when they were not protected. 191 Wearing the facemask was also associated with increased HRV, which suggests that the rapid BP-raising effects of particle inhalation may be mediated through the autonomic nervous system (ANS). In a similar fashion, 192 reducing exposure to particulate pollution from cooking stoves was shown to be associated with lower systolic (3.7 mm Hg, 95% CI Ϫ8.1 to 0.6 mm Hg) and diastolic (3.0 mm Hg, 95% CI Ϫ5.7 to Ϫ0.4 mm Hg) BP among Guatemalan women than among control subjects after an average of 293 days.…”
Section: Systemic and Pulmonary Arterial Bpmentioning
confidence: 99%
“…(7) However, the protective value of PPE has to be weighed against the physiological and psychological burden it imposes on the user. Respirators have been shown to provide beneficial cardiovascular effects through reducing exposure to particulate air pollution, (8) but they can also have physiological and psychological effects. After one hour of FFR use, carbon dioxide (CO 2 ) levels, temperature and humidity can be significantly elevated in the dead space within the FFR even as oxygen levels are lowered to levels below ambient workplace standards.…”
Section: Introductionmentioning
confidence: 99%